ESTIMASI CADANGAN KARBON PADA TUTUPAN LAHAN HUTAN SEKUNDER, SEMAK DAN BELUKAR DI KOTA SAMARINDA - Zikri Azham (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Estimation of Carbon Stock in Secondary Forest Land Cover, shrubs and thickets in Samarinda. Climate change mitigation efforts have been conducted, among others in the field of land is to be able to maintain the rate of conversion of vegetated land into another use, the role of CO2 absorbent vegetation becomes an important part at this time in order to overcome the global warming. Carbon absorbed by the plants is stored in the form of wooden biomass, so the easiest way to increase carbon stocks is by planting and maintaining trees also maintaining the land in order to keep it vegetated, therefore it is necessary to have carried out research aimed suspect carbon reserves on the type of cover land either shrubs, thickets and secondary forests, in Samarinda city. The study was conducted by the plot and the data retrieval with destructive and non-destructive and the analysis calculations using allometric. By the results of the study, it was found that the estimation amount of reserves of biomass on land cover in the form of Secondary Forest is the largest that is 203.826 tons/hectare, then the biomass in vegetation undergrowth of 74.180 tons/hectare and the third on vegetation shrub that is equal to 56.306 tons/hectare, On the third closure of the land and from the various components of the biomass vegetation, trees with a diameter 2cm up  have the largest biomass content as carbon sinks through the process of photosynthesis is 27.026 tons/hectare, 55.308 tons/ hectare and 137.473 tons/hectare, while rooting ranks second. Same as the content of the biomass, carbon stock estimation is the largest in land cover in the form of secondary forests, thickets and shrubs, are respectively 95.798 tons/hectare, 42.667 tons/hectare and 26.464 tons/hectare. Carbon content estimation on top (Above Ground Carbon) each respectively based on the order of the land cover is 69.93 tonnes/ hectare, 31.14 tons/hectare and 19.32 tons/hectare.